Women Empowerment and Indian Economy - Ms. Rajni Goel (Journal of the Oriental Institute, ISSN:0030-5324 UGC CARE Group 1, 2024)
India has the third largest ecosystem in terms of startups in the world and 10% of them have been led by Women founders. Indian women, despite constituting 48 % of the population, contribute only 18 % to the gross domestic product (GDP), found a study by the National family Health Survey. Bridging the gender gap in employment could potentially lead to a 30% increase in the country‘s GDP, invest in policies and social protection systems to create an enabling environment for women to enter and command in the formal and informal labour market such as family leave, daycare, flexible work hours and social serenity. Women are the backbone of the families and communities. They provide care, support and nurturing to their families and are essential to the development of Children. Women also play a significant role in community building and often take on leadership roles in community organizations. Present paper is an attempt to discuss women empowerment and role of women in Indian Economy.